In vitro analysis of microbial contamination of paper points - Renata Ximenes Lins1; Fanor Marques Junior; João Marcelo da Silva Teixeira; Georgiana Amaral; Luciana Moura Sassone (Revista Sul-Brasileira de Odontologia, 2015)
During endodontic treatment, the maintennance of the aseptic chain is mandatory. Therefore, all substances, instruments, and medications inserted into root canals must be free of microorganisms. Objective: To evaluate in vitro and microbiologically the contamination of absorbent paper points. Material and methods: Absorbent paper points of different brands and under different conditions were evaluated and subdivided into the following groups: esterilized by the manufacturer (G1 to G5), not esterilized by the manufacturer (G6), esterilized in autoclave by the operator (G7), and intentionally contaminated (G8). The two last groups were the positive and negative controls, respectively. All paper points were unpacked and immersed into tubes with culture medium for 48 hours and then analyzed according to culture broth turbidity. Results: Only the samples esterilized by the manufacturers Dentsply® (G1), Endopoints® (G2), and Meta® (G3), and the samples esterilized in autoclave by the operator (G7) did not evidence microbial growth after 48 hours. G7) did not evidence microbial growth after 48 hours. ) did not evidence microbial growth after 48 hours. Although sterilized by the manufacturer, both the brands Tanari® (G4) and Roeko® (G5) showed bacterial contamination; Dentsply® (G6) non-sterile paper points also showed bacterial contamination. non-sterile paper points also showed bacterial contamination. Conclusion: Paper point esterilization before clinical use should be Paper point esterilization before clinical use should be recommended regardless of the commercial brand.